Phenolic Compounds: Extraction, Optimization, Identification and Applications in Food Industry (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Interest has grown regarding natural plant extracts in food and beverage applications, their vital role in the food industry, and their therapeutic use against diseases. The protective effects of healthy diets are partially due to the variety of plant metabolites, particularly phenolic compounds, which are considered the most important class of compounds that originates from plant-derived metabolites. Phenolics are well renowned for their possession of a wide array of remarkable biological properties. This Special Issue (SI) aims to gather the most recent contributions concerning their chemistry, extraction methods, and analytical techniques, applications, and biological activities. This Special Issue of Processes, entitled “Phenolic Compounds: Extraction, Optimization, Identification and Applications in Food Industry”, gathers the recent work of leading researchers in a single collection, covering a variety of theoretical studies and experimental applications and focusing on the extraction, identification, and industrial applications. The advances presented in the contributions in this SI have significantly helped to accomplish this target. In addition to research articles, the Special Issue features two reviews that cover a range of topics highlighting the versatility of the area. The topics covered in this SI include advanced methodologies for the isolation, purification, and analysis of phenolics from food, food waste, and medicinal plants; biological activities and mechanisms of action; health benefits from in vivo evaluation; and the development of novel phenolics-based nutraceuticals and functional ingredients.